Genotyping Method and Frequency of ADRB3-rs4994 Single Nucleotide Polymorphism Genotypes in Hanoi 3-5 Years Old Chidren - Nguyen, Thi Hong Hanh (H. : ĐHQGHN, 2019)
The Trp64Arg (rs4994) polymorphism in codon 64 of ADRB3 (beta3-adrenergic receptor) gene is involved in the regulation of energy metabolism. This study optimizes the genotyping method of ADRB3 rs4994 polymorphism and determines the allele and genotype frequencies of this polymorphism in 3-5 years old children in Hanoi. A cross-sectional study was conducted on 100 three-to-five-year-old Hanoi children, using DNA extraction method from cheek mucosa cells. The genotyping of this polymorphism was performed by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) method. The study optimized the method of genotyping of ADRB3 rs4994 polymorphism with Mval enzyme. In 3-5 years old children in Hanoi, T/T genotype accounted for the highest proportion (78%), C/C genotype accounted for the lowest proportion (3%). T and C allele frequencies were 0.785 and 0.125, ​​respectively. The genotypes observed were in agreement with those expected under Hardy-Weinberg equilibrium. It is necessary to apply the genotyping method and genetic distribution for genotyping the ADRB3 rs4994 polymorphism in large-scale studies in Vietnam